Protocols of nursing assistance: a proposal to improve the quality of care in the mother and child internment unit - Aquino, Daise Ribeiro; Lunardi Filho, Wilson Danilo (Rev Rene, 2005)
Nursing has been undergoing a process of pursuit of appraisal as professional category. When planning care, it defines its role amongst the health professions. By registering the planned interventions through the Prescription of Nursing, it will materialize the existing connotation that the register belongs to the indispensable actions to therapeutics and therefore it needs to be registered in written form. Pursuing the improvement of planning, the System of Support to Decision in the Planning and Prescription of Nursing Care (SAD-PPCE) was created, a computational tool that depends on the development of Protocols of Nursing Assistance Guided to the Solution of Problems for its implementation. In order to do that, some protocols were elaborated in the period from September to December of 2002, in the Maternal-Infant Inpatient Unit of a university hospital, which demonstrate the amplitude and variability of the possible and necessary nursing actions at the hospital level.